2014
DOI: 10.1093/glycob/cwu027
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with recombinantly expressed glycan antigens from Schistosoma mansoni induces glycan-specific antibodies against the parasite

Abstract: Schistosomiasis caused by infection with parasitic helminths of Schistosoma spp. is a major global health problem due to inadequate treatment and lack of a vaccine. The immune response to schistosomes includes glycan antigens, which could be valuable diagnostic markers and vaccine targets. However, no precedent exists for how to design vaccines targeting eukaryotic glycoconjugates. The di- and tri-saccharide motifs LacdiNAc (GalNAcβ1,4GlcNAc; LDN) and fucosylated LacdiNAc (GalNAcβ1,4(Fucα1-3)GlcNAc; LDNF) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 92 publications
(111 reference statements)
3
29
1
Order By: Relevance
“…These global profiling studies have confirmed the major glycan structures previously identified and provided new information on the diversity of glycans and the heterogeneity found among the life stages of the parasite and their secretions (27,(29)(30)(31). Several studies also have demonstrated the feasibility of profiling schistosome glycans using various microarray printing technologies and probing with glycan-binding proteins, antibodies, and antisera, demonstrating that such techniques can be powerful tools for profiling the immune response to this disease (26,(32)(33)(34) and the development or characterization of novel anti-glycan reagents. The combination of these techniques, i.e., glycomics and/or glycan structural profiling, which is guided by the use of immunologically relevant reagents, such as antisera and MAbs, has great potential to improve our understanding of the anti-glycan response and uncover novel, immunologically relevant diagnostic and vaccine candidates.…”
supporting
confidence: 59%
See 4 more Smart Citations
“…These global profiling studies have confirmed the major glycan structures previously identified and provided new information on the diversity of glycans and the heterogeneity found among the life stages of the parasite and their secretions (27,(29)(30)(31). Several studies also have demonstrated the feasibility of profiling schistosome glycans using various microarray printing technologies and probing with glycan-binding proteins, antibodies, and antisera, demonstrating that such techniques can be powerful tools for profiling the immune response to this disease (26,(32)(33)(34) and the development or characterization of novel anti-glycan reagents. The combination of these techniques, i.e., glycomics and/or glycan structural profiling, which is guided by the use of immunologically relevant reagents, such as antisera and MAbs, has great potential to improve our understanding of the anti-glycan response and uncover novel, immunologically relevant diagnostic and vaccine candidates.…”
supporting
confidence: 59%
“…mansoni-infected Biomphalaria glabrata snails, strain NMRI NR-21962, were provided by the Schistosome Research Reagent Resource Center through BEI Resources, NIAID, NIH. Snail maintenance, collection of cercariae, transformation to schistosomula, and isolation of adult worms from mice were conducted as previously described (34,46). The schistosomula were cultured for 2 to 3 days in DMEM with 10% fetal bovine serum (FBS) and penicillin-streptomycin at a density of 500 to 1,000 organisms/ml in tissue culture dishes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations